HUKUMAN MATI BAGI ORANG YANG MURTAD DALAM PERSPEKTIF HADIS - Mutawali, Muhammad (Ahkam: Jurnal Hukum Islam, 2020)
Many Muslims who come out of their religion and embrace other religions with a variety of motives and reasons depending on their respective interests. This phenomenon seems to be a trend and lifestyle in the midst of the swift currents of globalization, democratic life, respect for Human right and religious freedom. In Islamic Criminal Law, apostasy (murtad) is a crime that is included in jarimah hudud. The punishment for apostates/riddah is the death penalty, and in the hereafter will get a reply in hell, this is in accordance with the message contained in the Qur'an and the Hadith of the Prophet Muhammad. This article explains the differences of opinion of the ulama regarding the punishment for the perpetrators of riddah / apostasy. Al-Qur'an does not specifically explain the punishment for apostates, it only stipulates the vanity of charity and in the hereafter will be given severe punishment. In the hadith of the Prophet which expressly punishes apostates with the death penalty. From the two sources of Islamic law as if there was a conflict. Therefore, it is very interesting to study considering that the problem of riddah is one of the problems in the study of Islamic criminal law which is always a concern of ulama and experts in contemporary Islamic law. Keywords: Riddah/Apostasy, Death penalty, Jarimah, Ta`zir